STUDY ON THE PREVALENCE OF CRYPTOSPORIDIUM IN CALVES SUFFERING FROM DIARRHEA IN NORTHWESTERN SYRIA - Hazem Faaz Altaweel; Fouad Al-Daoud; Gohar Mushtaq (Journal of Animal and Plant Sciences, 2023)
Cryptosporidium is one of the most common causes of diarrhea in calves worldwide, and the risk factors contributing to its control and prevention are extensively studied. This epidemiological study was conducted in an unstable breeding environment. Ninety-six (96) calves suffering from diarrhea were studied from five regions in northwestern Syria. The goal of this study was to assess the prevalence of cryptosporidium in fecal samples and to measure the expected risk and regression for assumed risk factors that may cause diarrhea in calves up to 60 days old. Fecal samples were tested using direct ELISA. The results showed 9.1% (1/11) cases in the western Aleppo countryside, 21.1% (4/19) in the eastern Idlib countryside, 13.6% (3/22) in the Northern Idlib countryside, 2.9% (1/35) in the Jisr Al-Shughur countryside, while no positive case was recorded in the western countryside. This is the first study conducted in the region showing the incidence, regression, and risk rates, and it accentuates the need for a broader study on the effect of certain drugs used in the treatment of diarrhea and its consequences.
Keywords: newborn calves; diarrhea; multiscreen ELISA; Cryptosporidium